Transvestism, transsexualism in the psychoanalytic dimension - Ambrosio, Giovanna (Controversies in psychoanalysis., 2009)
'From time to time we listen to some curious views on psychoanalysis as an old fashioned and useless discipline, more important from an historical perspective than as a tool for understanding human life in its normal and pathological dimensions, as well as an effective therapeutic instrument. This book on transsexualism and transvestism shows exactly how psychoanalysis can reflect, discuss, dialogue and formulate useful insights on one of the most challenging situations that nowadays confront all members of the mental health community. Giovanna Ambrosio assembled this group of distinguished an.